THE DYNAMICS OF ACTINOBACTERIA COMMUNITY DURING COMPOSTING - Mukhlissul Faatih (Pusbindiklat - LIPI, 2012)
The mesophilic, thermophilic, and maturation phases were recognized in the composting process. Temperaturechanges in the process influence the microbial communities in compost. Actinobacteria account for a largerpart of compost microbial population. The aim of this research was to study of Actinobacteria community duringcomposting of dairy-farm waste. Actinobacteria from the compost were isolated using selective media, starchnitratemedium and humic-acid+vitamins medium. The colour of colony and medium pigment were characterizedusing culture-dependent method. The results showed, total and resident Actinobacteria isolates from mesophilicphase is 29 and 24 isolates, 23 and 16 isolates from thermophilic phase, while 19 and 9 isolates from maturationphase. Twenty two isolates found in more than one phase. Thus, the dynamics of Actinobacteria was occurredwithin composting process.